2006
DOI: 10.1096/fj.05-4642fje
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone mediates angiotensin II‐induced interstitial cardiac fibrosis via a Nox2‐containing NADPH oxidase

Abstract: Angiotensin (ANG) II (AngII) and aldosterone contribute to the development of interstitial cardiac fibrosis. We investigated the potential role of a Nox2-containing NADPH oxidase in aldosterone-induced fibrosis and the involvement of this mechanism in AngII-induced effects. Nox2-/- mice were compared with matched wild-type controls (WT). In WT mice, subcutaneous (s.c.) AngII (1.1 mg/kg/day for 2 wk) significantly increased NADPH oxidase activity, interstitial fibrosis (11.5+/-1.0% vs. 7.2+/-0.7%; P<0.05), expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
208
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(237 citation statements)
references
References 54 publications
(56 reference statements)
21
208
0
7
Order By: Relevance
“…To further elucidate the underlying molecular mechanism, we examined the effect of ASK1 deficiency on NADPH oxidase subunits Nox2, Nox4, and p22-phox and found that ASK1 deficiency significantly prevented aldosterone-induced cardiac Nox2 upregulation. Taken together with the fact that Nox2 deletion in aldosterone-infused mice significantly attenuates cardiac NADPH oxidase activity and superoxide and markedly lessens cardiac inflammation and fibrosis, 25 our present results support the notion that the amelioration by ASK1 deficiency of aldosterone-induced cardiac NADPH oxidase activation seems to be at least partially attributed to the attenuation of Nox2 upregulation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To further elucidate the underlying molecular mechanism, we examined the effect of ASK1 deficiency on NADPH oxidase subunits Nox2, Nox4, and p22-phox and found that ASK1 deficiency significantly prevented aldosterone-induced cardiac Nox2 upregulation. Taken together with the fact that Nox2 deletion in aldosterone-infused mice significantly attenuates cardiac NADPH oxidase activity and superoxide and markedly lessens cardiac inflammation and fibrosis, 25 our present results support the notion that the amelioration by ASK1 deficiency of aldosterone-induced cardiac NADPH oxidase activation seems to be at least partially attributed to the attenuation of Nox2 upregulation.…”
Section: Discussionsupporting
confidence: 88%
“…23,24 Aldosterone is well known to activate cardiac NADPH oxidase, resulting in an increase in cardiac reactive oxygen species. 8,[25][26][27][28] Very importantly, NADPH oxidase-mediated reactive oxygen species are mandatory for the development of aldosterone-induced cardiac inflammation and fibrosis, as shown by previous in vivo findings 25,[27][28][29] that direct NADPH oxidase inhibition prevents aldosteroneinduced cardiac inflammation and fibrosis. However, the underlying mechanism of aldosterone-induced NADPH oxidase activation in vivo remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Work from our laboratory revealed that interstitial cardiac fibrosis was significantly attenuated in Nox2−/− mice subjected to either sub-pressor or pressor infusion of angiotensin II for 2 weeks, in association with reduction in NADPH oxidase activity [10], [17] and [92]. Similarly, angiotensin II-induced interstitial fibrosis was inhibited in conditional Rac1 knockout mice [59] and ASK-1 knockout mice [67].…”
Section: Interstitial Fibrosismentioning
confidence: 90%
“…Increased ROS is also associated with left ventricular hypertrophy (LVH), and this correlated with overexpression of Nox2 in Angiotensin II-induced LVH, and, in pressure overload LVH, with both Nox4 [55] and Nox2 [56]. Aldosterone/Angiotensin IImediated interstitial cardiac fibrosis is mediated by Nox2-dependent ROS generation [57]. Nox enzymes are likely to contribute to the occurrence of and tissue damage seen in myocardial infarction by several mechanisms.…”
Section: B Nox Enzymes In the Myocardiummentioning
confidence: 99%